2016
DOI: 10.1042/bst20160146
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of phosphatase of regenerating liver (PRL)-3

Abstract: The phosphatase of regenerating liver (PRL)-3 is overexpressed in many human cancer types and tumor metastases when compared with healthy tissues. Different pathways and mechanisms have been suggested to modulate PRL-3 expression levels and activity, giving some valuable insights but still leaving an incomplete picture. Investigating these mechanisms could provide new targets for therapeutic drug development. Here, we present an updated overview and summarize recent findings concerning the different PRL-3 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Initially PRL-3 was proposed as a phosphatase for metastasis[ 40 ], but multiple pathways and mechanisms have been implied to exert the effects of high PRL-3 expression. PRL-3 is a member of the PRL protein tyrosine phosphatase family and is the most studied of these so far [ 6 , 41 ]. All (PRL-1, PRL-2 and PRL-3) promote proliferation, migration, invasion and metastasis[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially PRL-3 was proposed as a phosphatase for metastasis[ 40 ], but multiple pathways and mechanisms have been implied to exert the effects of high PRL-3 expression. PRL-3 is a member of the PRL protein tyrosine phosphatase family and is the most studied of these so far [ 6 , 41 ]. All (PRL-1, PRL-2 and PRL-3) promote proliferation, migration, invasion and metastasis[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Vogelstein’s group suggested that the PRL-3 gene (gene name: PTP4A3 ) is important for colorectal cancer metastasis as they found high levels of PTP4A3 expression in metastases from colorectal cancer compared to non-metastatic tumors and normal colorectal epithelium[ 5 ]. Studies have found PRL-3 to be associated with epithelial-mesenchymal transition (EMT) and cancer progression[ 6 ]. Other studies have shown PRL-3 to be associated with metastatic potential and poor prognosis in a large number of cancers[ 7 16 ], as well as being upregulated in myeloma cells[ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…All three PRLs, PRL1/2/3 promote cell proliferation, migration, invasion, tumor growth, and metastasis. 70 PRL3 is the most studied of the three PRLs and it is overexpressed in liver metastatic tissue from colon cancer, but not in normal colon tissue. PRL-3 was also found to be overexpressed in many other human cancer types, such as melanomas, gastric, ovarian, breast, acute myeloid leukemia, and Hodgkin’s lymphoma.…”
Section: Role Of Ptps In Diseasesmentioning
confidence: 99%
“…PRL-3 was also found to be overexpressed in many other human cancer types, such as melanomas, gastric, ovarian, breast, acute myeloid leukemia, and Hodgkin’s lymphoma. 70 CD45 (lymphocyte common antigen), a class I receptor-like PTP, promotes antigen receptor signaling in lymphocytes. 71 CD45 and CD45-associated molecules play essential roles in T cell and B cell receptor signaling.…”
Section: Role Of Ptps In Diseasesmentioning
confidence: 99%
“…This modification is located on the catalytic cysteine, and in vivo it is abundant and persistent (Gulerez et al 2016;Zhang et al 2017). Phosphatases of regenerating liver play a causative role in cancer progression and metastasis, and thus deeper insight into the function of S-phosphorylation could be scientifically valuable (Rubio and Köhn 2016;Yu and Zhang 2018). Transient catalytic cysteine phosphorylation has also been reported for the protein tyrosine phosphatase, non-receptor type 12 (PTPN12) (Dong et al 2018) and the phosphoglucan phosphatase OsttaDSP from the green alga Ostreococcus tauri (Carrillo et al 2018).…”
Section: Introductionmentioning
confidence: 99%